Chitosan–Chitin Nanocrystal Films from Lobster and Spider Crab: Properties and Environmental Sustainability - Fernández Marín, Rut; Morales Matías, Amaia; Erdocia Iriarte, Xabier; Iturrondobeitia Ellacuria, Maider; Labidi Bouchrika, Jalel; Lizundia Fernández, Erlantz (ACS Sustainable Chemistry & Engineering, 2024)
The valorization of chitinous biomass from underutilized renewable carbon feedstock offers alternative routes for bioproduct development, reducing our dependence on nonrenewable and nonbiodegradable materials composed of fossil carbon. This work utilizes crustacean waste consisting of inedible shells to isolate chitin and its derivatives, chitin nanocrystals and chitosan, from lobster (Homarus gammarus) and spider crab (Maja squinado) shells. Chitin nanocrystals (ChNCs) with a degree of acetylation >93% and crystallinity >90% were obtained by demineralization, deproteinization and acid-hydrolysis, while chitosan was obtained by chitin deacetylation. Free-standing chitosan/ChNCs films were then fabricated from lobster and spider crab after dissolution and casting using 1.5% v/v formic acid. Lobster-derived materials exhibited a good balance between UV-shielding ability, blocking >96% of UV-C and UV-B, while being transparent at visible wavelengths. Neat chitosan films are semiductile, with elongations at break >13% and Young’s modulus values of 2.3 ± 0.7 and 3.4 ± 1.2 GPa for lobster and spider crab-derived chitosan, respectively. Besides, the incorporation of ChNCs increases the Young’s modulus to 5.5 ± 0.8 GPa at 2 wt % for lobster-derived films. Life cycle assessment (LCA) was conducted to quantify the environmental impact of film production and identify process hotspots for future optimization. A carbon footprint of 79.8 kg CO2 equiv·kg–1 is obtained for chitosan/ChNC films processed using a 100% renewable energy mix. Results demonstrate that lobster-derived materials are relevant contenders toward defossilization by developing renewable-carbon containing bioproducts with competitive performance against fossil-based materials due to their optical and mechanical properties, as well as their potential biodegradability. Financial support from the “2021 Euskampus Missions 1.0. Programme” granted by Euskampus Fundazioa is acknowledged. The authors are thankful for funds from the University of the ...